Contested spaces and sectarian narratives in post-uprising Bahrain. Issue 4 (1st October 2016) - Kasbarian, Sossie; Mabon, Simon
ABSTRACT: In early February 2011, people took to the streets of Manama, Bahrain, protesting against the political system of the Al Khalifa monarchy. Although initially occurring along non-sectarian lines, the protests were quickly framed as such and, as a consequence, the nature of the protests changed. This article engages with this process of sectarianism, exploring how space became contested and how such sites took on political – and sectarian – meanings. In the article, we argue that by framing the protests in such a way, the Al Khalifa regime was able to create a master narrative that impacted upon all facets of Bahraini society, at home and abroad.